(3OjhGf GHf GdaGQVs - (3GHf GdaGQV (B- (3SdWGf GdYGTbjf , YeQ Hf Ydj Hf eQTO Hf Ydj GdMehj, TQa GdOjf CHh MaU CHh GdbGSe,J (B632 (3g` s
(3ChdgG (B:s
(3bGd Ydi SHW GdTjN GHf GdaGQV fXQJ aj fSN ef OjhGf TjNfG bOS Gddg SQg aQCjJ GdfSGN LgdhG HYV cdGeg heG YQahg, hGTJHg Ydjge TF ef LfGSg aUMahg s
(3BNQgG (B:s
(3OGQ GdSdGe CdjgG bO hUdJ EPG ef SHd CHhGH EjeGfj hESdGej jGQHfG CQfj CfXQ Edjg HgG YfO GdbOhe hYGedfj HEcQGe s
(3GdfSNI HgG MhGTs
(3YdjgG JedjcGJ eDQNI aj (B962 (3g` hbQGAGJ eNJdaI s
(3hYdi ghGeTgG hHjf SWhQgG JYdjbGJ hTQhMs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs